Microfinance Cooperation Base On Loan Sharks - Hasan, Asyari; Prasetyowati, Riris Aishah (International Journal of Supply Chain Management, 2025)
This study aims to observe the motivational factors for the moneylender business of the Batak tribe known as shark loans. The discriminant analysis method is used to classify motivation into two different factors based on the pull and push theory. The testing was also carried out on two different groups of respondents, namely the favorable and the unfavorable. These results show that the determining factors for the motivation of borrower customers in the loanshark cooperative in this case are divided into two parts, namely; 1) pulling factors consisting of; independence, money, challenges/achievements, seeing opportunities, and lifestyle. 2) driving factors consisting of; job dissatisfaction, changes in the world of work, assistance from employers, and the needs of children/families. The results of the study prove that overall, all of these determining factors contribute to the Batak moneylender business. The Batak moneylender business based on the motivation factor of the pull and push theory in both community groups that support and oppose the Batak moneylender business shows that its existence is still very much needed, reaching 66.5%. Because the weak economic community in general do not have access to banking and do not have adequate requirements for creditworthiness or bank loans.